2009
DOI: 10.2134/agronj2008.0118x
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Straw Removal through Baling and Measuring the Long‐Term Impact on Soil Quality and Wheat Production

Abstract: Crop residues are considered the feedstock of choice for the production of ethanol, but removing crop residues may negatively impact soil productivity. Th e objectives were to quantify the proportion of total aboveground crop residues removed through baling and to evaluate the eff ects of 50 yr of straw removal with baling on soil quality and wheat (Triticum aestivum L.) production. Th e fi rst study evaluated three harvesting systems and their impact on straw removal with baling. Th e second study measured st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 26 publications
3
21
3
Order By: Relevance
“…In northern production areas, and if yields are high, up to 60% of corn stover can be safely harvested (Graham et al 2007). In a Canadian study, 40% of wheat residue could be harvested in 2 years out of three without affecting soil productivity (Lafond et al 2009). In cool climates, such as Finland, where the growing season is short and crop residues on the soil surface can reduce crop yields by slowing soil warming, their removal at least partly could even enhance yield formation.…”
Section: Sustainability Of Residue Collection For Bioenergymentioning
confidence: 99%
“…In northern production areas, and if yields are high, up to 60% of corn stover can be safely harvested (Graham et al 2007). In a Canadian study, 40% of wheat residue could be harvested in 2 years out of three without affecting soil productivity (Lafond et al 2009). In cool climates, such as Finland, where the growing season is short and crop residues on the soil surface can reduce crop yields by slowing soil warming, their removal at least partly could even enhance yield formation.…”
Section: Sustainability Of Residue Collection For Bioenergymentioning
confidence: 99%
“…Unfortunately, farm and field-level economic analyses are often limited or are not being conducted [10][11][12]. In those cases where economic analyses were conducted, it was generally for only one or two sites [3,7], thus limiting the potential to identify common patterns across locations and requiring substantial analyst time to assemble the same basic economic information needed for analysis at each location.…”
Section: Introductionmentioning
confidence: 99%
“…[10,[17][18][19]27,28,31,[37][38][39][40][41][42][43][44][45] Such research relates largely to management of corn stover and wheat straw in North America. [17][18][19][26][27][28]31,[39][40][41][42] Corn harvests generate relatively large amounts of corn harvest residues if compared with oil seed crops such as soya bean and cereal crops such as wheat, rice, barley, oats and sorghum, and this might allow for a relatively large removal of harvest residues without a negative effect on soil carbon stocks. [39] Wilhelm et al [31] concluded that within limits corn stover can be removed for ethanol production, with the actual limits being dependent on regional yield, topography, climatic conditions and agricultural practices.…”
Section: Introductionmentioning
confidence: 99%
“…[40] There have also been empirical studies about the effects of wheat straw removal on the upper 15.2 cm of soils belonging to a Canadian research farm at Indian Head which were managed under a long-term notill system. [41,42] From these studies it was concluded that wheat straw removal should be <40%, and presumably in the order of 22%, of aboveground residues other than grain and not more frequent than two out of three years. [41,42] It might be that the estimates regarding the acceptable removal of harvest residues in the studies discussed so far [27,31,[39][40][41][42] might be insufficient to prevent soil compaction in no-till systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation